(untitled) (Atlas Journal of Biology, 2017)
A survey in the Mamora forest was done in the spring of 2010 and revealed that 67% of buds and 27% of leaves of Pyrus mamorensis (Trabut) samples collected had lesions with a gray felting. The pathogenic fungus was identified as Botrytis cinerea by the filter – paper technic. Koch´s postulate was verified by inoculating healthy leaves. The estimated disease severity on P. mamorensis leaves was respectively 75.56% and 68.81% for inoculation by conidial suspension and the mycelial disks. Conidia production of Botrytis cinerea on inoculated leaves by conidial suspension was 1.03.105 conidia.cm-2 and by mycelial disks was 0.60.105 conidia.cm-2. This was the first report of gray mold disease of Mamora pear caused by Botrytis cinerea in Morocco.